Pengaruh Kompetensi SDM, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Kantor Nagari Se Kecematan 2x11 Enam Lingkung - Aysusi Haripan Suvi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study investigates in depth the influence of human resource (HR) competency, work discipline, and work motivation on employee performance in Nagari Offices throughout the 2X11 Enam Lingkung District. In the context of the globalization era, an agency's ability to survive and thrive depends heavily on the quality of its human resources. Optimal performance is key to success, and internal factors such as competency, discipline, and work motivation are often the primary determinants. This research was motivated by several performance issues identified in the field, such as employees' lack of understanding of their main tasks and functions (tupoksi), difficulties in measuring Employee Work Targets (SKP), and a decline in attendance and discipline levels. Using a quantitative approach, this study collected primary data through questionnaires distributed to the entire employee population, namely 25 people, using a saturated sampling method. The data were analyzed using multiple linear regression analysis and processed using SPSS version 26. The analysis results show that the three independent variables—competence, work discipline, and work motivation—partially and simultaneously have a positive and significant influence on employee performance. The Adjusted R Square value of 83.1% indicates that this research model is very strong in explaining variations in employee performance, where the remaining 16.9% is influenced by other factors outside the scope of the study. This finding emphasizes the importance of comprehensive HR management, including competency development, discipline enforcement, and motivation enhancement, to achieve optimal organizational performance.